Comparative Analysis of ART in the EU: Cross-border Reproductive Medicine - Stanić, Gordana Kovaček (Medicine, Law & Society, 2015)
The need for cross-border reproductive medicine exists for several reasons. Some are due to the fact that some states do not permit particular ART procedures; thus couples travel to the state where needed procedure is allowed (surrogate motherhood, embryo donation, posthumous fertilization). Other situations are due to the fact of who is entitled to ART procedures. In some states ART procedures are not allowed to same-sex couples or a single woman. The consequence of the cross-border reproductive medicine might be that the born child becomes parentless (“limping legal parentage”) and stateless. Since the best interest of the child is the paramount principle in contemporary family law, it is most important to find solutions for these situations. The most complicated issues are the consequences arising from international surrogacy arrangements. The Hague Conference on private international law is working on these issues trying to find the best solutions.
Keywords: cross-border; reproductive medicine; child; parentage; Hague Conference; EU